Morphological study of the sensory nerve which induces jaw opening reflex - Rie Shimotakahara; Kazuharu Mine; Shigemitsu Ogata (Wolters Kluwer Medknow Publications, 2015)
Background and objectives: An anatomical site in the oral cavity can be used to trigger the jaw opening reflex in patients with pseudobulbar palsy who have difficulty opening the mouth. The site is located at the midpoint between the palatoglossal arch and pterygomandibular fold and medial to the retromolar pad. However, previous findings on the nerves innervating this particular area are inconsistent. Therefore, in this study, we carefully investigated the sensory nerves that innervate the area near the trigger point of the jaw opening reflex. Materials and methods: For the morphological investigation of sensory innervation in this area, in this study we exposed the cranial nerves in 26 halves of cadaver head and observed their distribution in soft tissue. Results: In all cases, several nerve fibers diverged anteroinferiorly from the lingual nerve located between its junction with the chorda tympani nerve and the junction with the communicating branch of the submandibular ganglion. These nerve fibers, thought to be the facial branches of the lingual nerve, innervated the mucosa in the vicinity of the palatoglossal arch, retromolar pad, and the lingual gingiva of the last molar which were near to the trigger point of the jaw opening reflex. Conclusion: The results suggest that the sensory nerve that induces the jaw opening reflex appears to be the branches to isthmus of fauces diverged from the lingual nerve.